If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+5=12+4x/2
We move all terms to the left:
3x+5-(12+4x/2)=0
We add all the numbers together, and all the variables
3x-(4x/2+12)+5=0
We get rid of parentheses
3x-4x/2-12+5=0
We multiply all the terms by the denominator
3x*2-4x-12*2+5*2=0
We add all the numbers together, and all the variables
-4x+3x*2-14=0
Wy multiply elements
-4x+6x-14=0
We add all the numbers together, and all the variables
2x-14=0
We move all terms containing x to the left, all other terms to the right
2x=14
x=14/2
x=7
| 3.5=25x | | 3.4+10m=8.38 | | 5+7n=-15+3n | | 38(-3c+4)=2(1c=+5)+1c | | -5v+2(v+5)=1 | | 4x-2(3x-2)=6x+8x=-0.5. | | 9-4.5-0.6x=9.3 | | 3(2x-6)=-36+12 | | 8(9-x)+12=648(9-x)+12=64 | | 3x(x+1)+4x+3=34 | | 5x=(6x°2) | | 8n-13=7n-8 | | 3=1+7a | | -226=-14x | | 15=0.5(x+2)-3 | | 4x-2(3x-2)=6x+8 | | (m-4)2=16 | | 4-x/2=-8 | | 5(x-5)+1=5x-14 | | -5(x-1)+5(-3x-8)=25 | | 5x+-10=8+5x | | 4+2m=4+6m | | 2x-9=-x-11 | | (y+2)/3=3 | | -3m-6-m=10 | | 5/8+1/3x=69 | | -2x-9=-x-11 | | 4x+6(x-3)+21=93 | | -5(5x+7)+1=-109 | | 4s=2.8(s+3) | | -5-8h+3=2h+8 | | 4x×116=180 |